Mapping the intangible: Using geolocated social media data to examine landscape aesthetics - Langemeyer, Johannes; Calcagni, Fulvia; Baró, Francesc (Land use policy, 2018)
•We used social media data from Flickr to map landscape aesthetic flow.•We used stated and revealed preferences to compare landscape aesthetic capacity and flow .•We found human built infrastructure does not negatively influence landscape aesthetic flow.•Accessibility is assumed one of the key factors to guarantee landscape aesthetic flow. The ecosystem services concept is increasingly gaining momentum in land-use policies and landscape planning. Yet, cultural ecosystem services often lack proper assessments. With this study, we use novel methodological approaches to map the cultural ecosystem service landscape aesthetics for its enhanced consideration in land-use policies. Our study uses expert-based participatory mapping and crowd-sourced (social media) photo data to examine the spatial distribution of landscape aesthetics in the Province of Barcelona, Catalonia. We distinguish the capacity and flow of landscape aesthetics. Landscape aesthetics capacity was assessed through spatial multi-criteria evaluation, consisting of a viewshed analysis and an expert-based selection and weighting of landscape features. Landscape aesthetics flow, i.e., people’s actual appreciation of landscape aesthetics, was assessed by analysing a sample of 13,460 geolocated photographs from the social media platform Flickr. Our results uncover a substantial mismatch between landscape aesthetics capacity and flow. While landscape aesthetics capacity is widely distributed across the case study area, landscape aesthetics flow is (with few exceptions) mostly concentrated in urban and periurban areas. The main insights for land-use policies derived from our results are twofold. On one hand, landscape aesthetics flow seems less dependent on ‘pristine nature’ than experts and planners assume, while the complex integration of green and grey landscape features plays a critical role. On the other hand, urban and periurban landscapes as key landscape aesthetics providers should receive additional attention in land-use policies.